Uma contribuição à avaliação de desempenho dos principais métodos para a atribuição de responsabilidades sobre as distorções harmônicas - Santos, Ivan Nunes (2007)
The subject power quality contemplates diverse aspects relative to the conformity of the product electric energy, in special, the voltage. Amongst the subjects that are treated under such assignment, it is the question of the harmonic distortions, which in the present time have increased considerately in the most distinct constituent points of the electrical systems. Therefore, regulating agencies, concessionaires and consumers have shown an increasing concern on the reached levels for this pointer of the quality of the electric supply. For the harmful character of these riots, international and national norms and recommendations have looked for to establish limits for the distortions. These documents, in a general way, prime for the definition of values of reference for the pointers of the total and individual distortions, without, however, entering in the merit of the origin of the same ones. In these terms, a time evidenced a breaking of the established limits and defined the necessity of the implementation of a systematic of mitigating of the effect, appears the question of the financial responsibility associated to the process to be implemented. Inserted in this context, the subject is placed "sharing of responsibility", which consists of center of this work. Thus, this work meets directed to synthesize the state of the art on the subject, considering, above of everything, the main found proposals of sharing in literature, which is: Method of the Harmonic Power, Method of the Current Conforming and Non-conforming and Method of the Overlapping. To leave of these, using experimental and computational procedures, it is proceeded the evaluation and critical analysis from the suggested procedures, detaching its potentialities and limitations.